Diversification of the orchid genus Tridactyle: Origin of endemism on the oceanic islands of São Tomé & Príncipe in the Gulf of Guinea. (14th February 2022) - D'haijère, Tania; Kaymak, Esra; Boom, Arthur F.; Hardy, Olivier J.; Stévart, Tariq; Mardulyn, Patrick
Abstract: Aim: Oceanic islands have played an important role in our understanding of the diversification of organisms, and phylogenetic estimates have been used in this context to investigate the origin of island diversity and its relationship to the continent. Using a typical orchid genus rich in island endemics and with widespread continental relatives, we aim to compare alternative hypotheses of diversification with a focus on island endemism. Location: Tropical Africa and the Gulf of Guinea Islands of São Tomé & Príncipe, Central Africa. Taxon: Tridactyle genus (Orchidaceae). Methods: We used genome skimming to sequence the whole chloroplast genome and nuclear ribosomal genes from 157 individuals of 34 Tridactyle species and 15 individuals of 12 other orchid genera (outgroups) to infer a time‐calibrated phylogenetic tree of the genus Tridactyle . We also used multiple statistical methods to infer the geographical ranges of the ancestral nodes from the estimated phylogeny. Alternative hypotheses for the origins of endemism on the islands of São Tomé and Príncipe were investigated based on the biogeographical reconstruction of the genus. Results: The estimated phylogeny of Tridactyle and reconstruction of geographical ranges for the ancestral nodes suggested a general history of allopatric speciation for the genus, in particular via colonization of the islands of the Gulf of Guinea that induced a long period of geographical isolation. The most parsimonious hypothesis to explain island endemism in Tridactyle involved six independent colonizations of the islands from the continent. Main conclusions: In contrast to other cases of oceanic island endemism that involved adaptive radiation on an island or within an archipelago, endemism in Tridactyle is better explained by multiple colonization events from the continent to São Tomé and Príncipe, with subsequent divergences due to geographical isolation but only one potential instance of further diversification on the islands.